Effect of Ultraviolet Irradiation on the Pathogenicity of Fusarium moniliforme Pokkahboeng Disease on Sugar Cane - Fahmy Fadly; Lahmuddin Lubis; Lisnawita Lisnawita (Universitas Sumatera Utara, 2019)
Effect of Ultraviolet Irradiation on the Pathogenicity of Fusarium moniliforme Pokkahboeng Disease on Sugar Cane. Pokkahboeng is the important disease on sugarcane and can reduce sugar production. This research was study to determine the effect of UV to pathogenicity of F. moniliforme. This research has conducted at green house of Faculty of Agriculture Universitas Sumatera Utara from July-October 2016 using completely randomized design (CRD) nonfactorial and five treatments: M0, M1, M2, M3, M4 (without UV exposure, UV exposure for 15, 30, 45, and 60 minutes) with four replications. The results showed that pathogenicity of F. moniliforme was declined after UV radiation and UV irradiation for 45 minutes was the most efficient time to suppress the pathogenicity of F.moniliforme. Key words : Fusarium moniliforme, sugarcane, ultraviolet